"Cimmero-Scythian" Antiquities from Central Anatolia - Маkhortykh, S.V. (Археологія і давня історія України, 2022)
The contribution discusses the artifacts of nomadic types from Central Anatolia which include weapons, horse equipment and objects made in the traditions of Scythian animal art style. They highlight the complex ethnic composition of the nomadic groups located here in the 7th—6th centuries BC that does not allow attributing all these archaeological materials to a single group, for example, the Cimmerians.